Engineers and engineering in the Renaissance - Parsons, William Barclay (M.I.T. Press, 1968)
Calls attention to the technical achievements in civil engineer, mining engineer, the invention of machines, river-control, canal-building, bridge-building, and structural engineering on the continent of Europe.
Pages 3 through 11 of the orig. ed. have been deleted
Keywords: Geschichte; Civiele techniek; Ingenieurs; Werktuigbouw; Ingenieurwissenschaften; Engineering -- Europe -- History; Renaissance; Technik; Europa